Lower abdominal and pelvic radiation and testicular germ cell tumor risk - Nead, Kevin T. (PLoS One, 2020)
BACKGROUND: Testicular germ cell tumor (TGCT) incidence has increased in recent decades along with the use and dose of diagnostic radiation. Here we examine the association between reported exposure to diagnostic radiation and TGCT risk. METHODS: We conducted a case-control study of men with and without TGCT recruited from hospital- and population-based settings. Participants reported on exposures to 1) x-ray or CT below the waist and 2) lower GI series or barium enema, which consists of a series of x-rays of the colon. We also derived a combined measure of exposure. We used logistic regression to determine the risk of developing TGCT according to categories of exposures (0, 1–2, or ≥3 exposures) and age at first exposure, adjusting for age, year of birth, race, county, body mass index at diagnosis, family history of TGCT, and personal history of cryptorchidism. RESULTS: There were 315 men with TGCT and 931 men without TGCT in our study. Compared to no exposures, risk of TGCT was significantly elevated among those reporting at least three exposures to x-ray or CT (OR(≥3 exposures), 1.78; 95% CI, 1.15–2.76; p = 0.010), lower GI series or barium enema (OR(≥3 exposures), 4.58; 95% CI, 2.39–8.76; p<0.001), and the combined exposure variable (OR(≥3 exposures), 1.59; 95% CI, 1.05–2.42; p = 0.029). The risk of TGCT was elevated for those exposed to diagnostic radiation at age 0–10 years, compared to those first exposed at age 18 years or later, although this association did not reach statistical significance (OR, 2.00; 95% CI, 0.91–4.42; p = 0.086). CONCLUSIONS: Exposure to diagnostic radiation below the waist may increase TGCT risk. If these results are validated, efforts to reduce diagnostic radiation doses to the testes should be prioritized.